2015
DOI: 10.1016/j.ehb.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Maternal pre-pregnancy BMI, gestational weight gain, and infant birth weight: A within-family analysis in the United States

Abstract: In the United States, the high prevalence of unhealthy preconception body weight and inappropriate gestational weight gain among pregnant women is an important public health concern. However, the relationship among pre-pregnancy BMI, gestational weight gain, and newborn birth weight has not been well established. This study uses a very large dataset of sibling births and a within-family design to thoroughly address this issue. The baseline analysis controlling for mother fixed effects indicates maternal precon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…1 Insufficient weight gain has been linked with increased risks of low birth weight, small for gestational age, and preterm birth, while excessive gain has been associated with large for gestational age, gestational diabetes, preterm birth, caesarean section, infant mortality, postpartum weight retention, and childhood obesity. [2][3][4][5][6][7][8][9] Pregnant women are therefore routinely weighed in clinical settings. The benefits of doing so, however, are debatable in the absence of appropriate guidelines or even agreement on what constitutes adequate weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…1 Insufficient weight gain has been linked with increased risks of low birth weight, small for gestational age, and preterm birth, while excessive gain has been associated with large for gestational age, gestational diabetes, preterm birth, caesarean section, infant mortality, postpartum weight retention, and childhood obesity. [2][3][4][5][6][7][8][9] Pregnant women are therefore routinely weighed in clinical settings. The benefits of doing so, however, are debatable in the absence of appropriate guidelines or even agreement on what constitutes adequate weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also indicated reduced the placental: fetal weight ratio (Heasman et al, 1998), undernutrition in early to mid-gestation (Faichney and White, 1987;McCrabb et al, 1991) and undernutrition in late gestation (Mellor and Murray, 1981) as an important factor for fetal and birth outcome. Pre-pregnancy body mass index and gestational weight gain are critical for optimal infant health (Kaiser and Allen, 2008;Yan, 2015). Successful weight gain modifications illustrate assure in dropping the risk of large for gestational age (LGA) which has subsequent risk of overweight, obesity, diabetes mellitus, malignancy, and other disorders afterward in life (Jessica et al, 2015) .…”
Section: Introductionmentioning
confidence: 99%
“…Pre-pregnancy BMI data were available 275 for 918 (78.3%) women whose data are presented here, 632 (69%) of whom were classed as 276 having a normal BMI, 232 (25%) as having a high BMI (154 women had a BMI of 25.0-29.9 277 kg/m 2 and 78 had a BMI≥30.0 kg/m 2 ), and 54 (6%) with a low BMI, 16 (30%) of whom had a 278 BMI below 17.5. For study purposes the overweight and obese categories were combined as 279 both include ranges of weight considered suboptimal for healthy pregnancy and birth outcomes 280 (Yan, 2015). The women who were of normal weight had a median BMI of 21.6 (IQR=20.4-281 22.9), the women who were overweight or obese had a median BMI of 28.3 (IQR=26.4-31.0), 282 and the women who were underweight had a median BMI of 17.7 (IQR=17.3-18.2).…”
Section: Statistical Methods 238mentioning
confidence: 99%